A Mindfulness‐Based Intervention: Differential Effects on Affective and Processual Evolution. Issue 3 (6th September 2018) - Antoine, Pascal; Congard, Anne; Andreotti, Eva; Dauvier, Bruno; Illy, Johan; Poinsot, Rollon
Abstract : Objectives: A 20‐minutes‐a‐day, self‐help, mindfulness‐based intervention was conducted for 6 weeks with a French community sample. First, the intervention effects on affective and functioning variables were evaluated. Then, a differential approach was used to examine improvement potentiality and the perceived benefits of mindfulness according to the participants' baseline mindfulness competencies. Method: Participants were non‐randomly assigned to a control group on the waiting list ( n = 44) or a mindfulness group ( n = 47). Self‐report measures assessed anxiety, depression, psychological distress, mindfulness, negative self‐oriented cognition, and experiential avoidance. Results: Improvements in the variables were observed for the mindfulness group but not for the control group, with effect sizes ranging between .53 and .88. Low baseline levels of mindfulness predicted greater improvement in mindfulness ( r = −0.55, p < .001) than high baseline levels. Conclusions: Mindfulness practice elicited several positive outcomes regarding affective variables, highlighting emotional functioning changes.